What are the main proteins in the hemolymph of Haemaphysalis flava ticks? - Li, Dan; Liu, Lei; Liu, Zi-ling; Tian, Yuan; Gao, Xin; Cheng, Tian-yin (Frontiers in Veterinary Science, 2024)
Background: Haemaphysalis flava is a notorious parasite for human and animals worldwide. The organs of H. flava are bathed in hemolymph which is a freely circulating fluid. The nutrients, immune factors and waste can be transported to every part of the body via hemolymph. The main soluble component in hemolymph are proteins. However, knowledge on the H. flava proteome is limited. Methods: Hemolymph was collected from fully engorged H. flava ticks by leg amputation. Hemolymph proteins were examined by both blue native polyacrylamide gel electrophoresis (BN-PAGE) and sodium dodecyl sulfate PAGE (SDS-PAGE). Proteins extracted from gels were further identified by a combination of liquid chromatography-tandem mass spectrometry (LC-MS/MS). Results: Two bands (380 kDa and 520 kDa) were separated from tick hemolymph by BN-PAGE and were further separated into four bands (105 kDa, 120 kDa, 130 kDa and 360 kDa) by SDS-PAGE. LC/MS/MS revealed that seven tick proteins and 13 host proteins existed in the four bands. These tick proteins mainly were the vitellogenin (Vg) family and αmacroglobulin family members. In silica structural analysis showed that these Vg family members all had common conserved domains including the N-terminus lipid binding domain (LPD-N), the C-terminus von Willebrand type D domain (vWD) and the unknown functional domain (DUF). Additionally, two of the Vg family proteins belonged to carrier protein (CP) by analyzing the unique N-terminal amino acid sequences and the cleaving sites. Conclusion: These findings imply that Vg family proteins and α-macroglobulin are the primary constituent of hemolymph in the form of protein complexes. Our results provide a valuable resource for further functional investigations of H. flava hemolymph effectors, and might be useful in tick management.